Assessing the performance of the CECO wave energy converter in the Portuguese near-shore - Paulo Rosa Santos (2017)
CECO is a novel Wave Energy Converter (WEC) concept, which has shown a large potential to capture wave energy. The present work focuses on assessing the performance of CECO alongside the Portuguese near-shore, considering both the local wave climate and the main operating characteristics of CECO. For this purpose, the CECO power matrices of absorbed wave power were constructed, using the BEM-based model ANSYS® AQWATM. Overall, it was found that CECO presents promising results, especially at relatively shallow waters and mild wave conditions with values of Captured Energy Efficiency exceeding 40 %. In addition, the results obtained offer some valuable insight into the future development of CECO with the purpose of addressing the limitations of the current design and to optimise its performance according to the wave conditions for specific locations